Primary psoas abscess due to Streptococcus milleri - Abeysekara Abeywardana MS; Bagul Nitin B; Jacob Sabu (BMC, 2008)
Abstract Primary Psoas abscess (PPA) is an infrequent clinical entity with obscure pathogenesis and vague clinical presentation. High index of clinical suspicion is required for the diagnosis of psoas abscess. We also emphasises the importance of bacteriological confirmation of microorganism involved, although Staphylococcus aureus remains the commonest pathogen. We report an extremely rare case of PPA caused by Streptococcus milleri. Only one case has been reported in literature so far.